Monitoring of quallity of essential oil from Etlingera SP.5 (Zingeberaceae) by GC/MS &GC - FID - Mohd Azlan, Mat Ali (2008)
The aim of the present study is to monitor the quality of the essential oil from Etlingera sp. 5 (ZINGIBERACEAE) using GC/MS & GC – FID which this research is has been never reported before. So by provided the effect of storage on the quality of the essential oil, which can be obtained by GC/MS & GC – FID, will also yield useful information on the product. This research objective are to extract essential oil from the rhizome material of Etlingera sp. 5 by hydro-distillation, to develop a method of analysis of essential oil from the rhizome material of Etlingera sp. 5 by using GC/MS & GC-FID, and to monitor the effect of storage on the quality of the essential oil. The essential oil was extract by using hydro distillation with Clevenger type. To measure the quality of the essential oil, two tests had been come out there were light test and temperature test where the fresh essential oil will be separated into two according to the two tests. Clear & colorless vial was use to see the effect of light while the dark brown vial was use to see the effect of temperature to the quality of the essential oil. This two test of vials were put into two different places in the same room whereas for the light test vial was put in the glass cabinet while the temperature test vial was put near to the window where expose to direct sunlight. This monitoring was done in 3 weeks duration to see the changes when we test to the light and the temperature at normal room condition. This monitoring takes one week interval to analyze using GC – FID and to determine the major compounds, GC/MS will be use to detect the compounds. From the results, three major compounds had been detected and been analyzed which are Nerolidol, Farnesol and 1 – Tricosene. These three major compounds seen to have a slight change to the light and temperature test within three weeks of monitoring of the quality of the essential oil from Etlingera sp. 5. As for the conclusion, due to expose to light and temperature test, quality of essential oil from the Etlingera sp. 5 is affected to light and temperature. To continued research, there are suggested that this research is done for a longer period of time to see the significant changes of the compounds and to determine the minimum quality of the essential oil base on the duration exposed.